Plasma Levels of Heat Shock Protein 90 Alpha Associated With Colorectal Cancer Development - Wei, Wene; Zhou, Jiahui; Chen, Lipeng; Liu, Haizhou; Zhang, Fuyong; Li, Jilin; Ning, Shufang; Li, Shirong; Wang, Chen; Huang, Yi; Zou, Chang; Zhang, Litu (Frontiers in Molecular Biosciences, 2021)
Aim: The role of plasma heat shock protein 90 alpha (HSP90α) in colorectal cancer patients remains unclear. This study aimed to evaluate the relationship between HSP90α and the occurrence and development of colorectal cancer through diagnosis and prognosis value. Methods: 635 colorectal cancer patients and 295 healthy controls were recruited. The HSP90α was measured by using the ELISA kit in all objects and the immune cells and common biomarkers as CEA, AFP, CA125, CA153 and CA199 were measured in all colorectal cancer patients. The relationship between plasma HSP90α with clinical features, common tumor markers and immune cells were also conducted. The survival analysis endpoint was progress-free survival (PFS). Results: The levels of plasma HSP90α were significantly higher in colorectal cancer patients compared to healthy controls (51.4 (ng/ml) vs. 43.7 (ng/ml), p<0.001). In additional, the levels of plasma HSP90α were associated with gender and disease progress as stage, lymphatic and distant metastasis. Furthermore, plasma HSP90α was closed correlation with CEA, CA125, CA199 and percentage of B cells. However, the initial expression level of plasma HSP90α failed to show a prognostic value for progress-free survival in colorectal cancer. Conclusions: The plasma Hsp90α was remarkable higher in colorectal cancer and correlated with common tumor biomarkers and immune cells. Plasma Hsp90α levels were associated with disease progress but a poor diagnosis performance and also failed to show a prognostic value in colorectal cancer.